2017
DOI: 10.1617/s11527-017-1030-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hybrid steel fiber reinforcement in high performance geopolymer composites

Abstract: In this paper, cement free high performance alkali activated slag-fly ash composites are designed by applying the modified Andreasen and Andersen particle packing model, and steel fibers of two lengths are applied for strength reinforcement and shrinkage compensation. The influence of the fiber length, dosage and hybrid on the fresh behavior, compressive strength, stress-stain behavior under flexural load, porosity and drying shrinkage are evaluated, and the gel structure of this blended alkali system is also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 49 publications
2
32
0
1
Order By: Relevance
“…Therefore, the fresh matrix requires more vibration to lose its harsh static mode and form the mold [27,101]. Some experiments showed that the critical value tends to decrease when the aspect ratio of fiber and filler volume is increased [126][127][128][129]. Furthermore, the high surface roughness and crimped or hook-end fibers result in a reduction in critical concentration and flowability [124,130].…”
Section: Workabilitymentioning
confidence: 99%
“…Therefore, the fresh matrix requires more vibration to lose its harsh static mode and form the mold [27,101]. Some experiments showed that the critical value tends to decrease when the aspect ratio of fiber and filler volume is increased [126][127][128][129]. Furthermore, the high surface roughness and crimped or hook-end fibers result in a reduction in critical concentration and flowability [124,130].…”
Section: Workabilitymentioning
confidence: 99%
“…Davidovits (Davidovits, 2005;Davidovits, 1994;Davidovits, 1991) was the first to synthesize fibre reinforced geopolymer concrete for their use in the plastic processing industry. This was furthermore extended by various other researchers, utilizing particular sorts of fibres, for instance, carbon and glass (Natali et al, 2011), polyvinyl alcohol (PVA) (Yunsheng et al, 2008;Nematollahi et al, 2015) polypropylene (PP) (Li et al, 2016), polyethylene (PE) (Nematollahi et al, 2017;Ahmed and Ronnie, 2017) and steel fibers (Gao et al, 2017;Ranjbar et al, 2016b;Li et al, 2016;Bernal et al, 2010;Ranjbar et al, 2016c) in a diverse range of geopolymers containing different source materials and alkaline solutions (Shaikh, 2013b). Subsequent, reinforcement of geopolymers with different type of fibres were carried on through protein-based fibres (Alzeer and MacKenzie, 2012), basalt fibres (Dias and Thaumaturgo, 2005), organic fibres like cotton, flax, etc.…”
Section: Introductionmentioning
confidence: 90%
“…This finding was also observed in [15] and [16] whereby the higher the steel fibre volume used in a fixed (steel + PE) combination, the higher the workability found. Meanwhile, Gao et al [17] characterized the slump flows of samples with 1% fibre volume content at different long/short fibre ratios (i.e., 80/20, 60/40, 40/60 and 20/80) and reported that higher long/short fibre ratio exhibited a relatively low slump. The information on the effect of fibre hybridization on the flowability of fresh FRG composites is rather limited, and apparently additional studies in this aspect need to be conducted due to its complexity.…”
Section: Hfrg Materials Constituents and Fibre Hybridizationmentioning
confidence: 99%
“…FA-based FRG composite is observed to be more workable than slag-based composite because of its inherently smooth spherical shape bringing a ball-bearing effect that reduces internal friction in the mixture. Other factors that influenced the workability condition of fresh FRG composites include fibre types and smoothness, fibre mechanical properties, alkaline activator properties, and other admixtures [7,17]. Tables 1 and 2) are the ones producing the highest strengths or toughness, nevertheless other combinations can be found in the individual concerned studies.…”
Section: Hfrg Materials Constituents and Fibre Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation